Free Will and Individualism in Parijat’s Blue Mimosa: An Existentialist Approach - Paudyal, Ganga Ram; Bhandari, Sabindra Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This paper explores Parijat’s novel Blue Mimosa (Shirish Ko Phool) from the perspective of existentialism, expounding the concepts of free will, authenticity and autonomy. The central characters Suyog Bir and Sakambari quest for a journey of identity relying on their free will for a self-created life. The novel depicts them as separate individuals having their own essence. They have wandered being guided by their own will, without compromising with the established norms. Implementing a qualitative approach to research, this paper reviews the related commentaries and books concerning Parijat and her novel Blue Mimosa. The novel, as a primary source, provides data and information about existentialism, revealing the impact of existence in the lives of the characters. Exploring the novel from the lens of existentialism, the present study delineated the issue of how the characters are involved in the choice of personal matters to create their own self rather than over-reliance on collective thoughts. Since existentialism emphasizes the deep personal convictions that guides the lives of people rather than making rational judgments; the life instincts of the characters, in the novel, become free will of life force to acknowledge how they have passed their lives. The findings of this study can have practical implications on real-life events, assimilating with the role of characters and realizing their stand as an independent self being guided by their free will rather than being attached to social norms.